Motion perception: a review of developmental changes and the role of early visual experience - Hadad, Bat-Sheva; Schwartz, Sivan; Maurer, Daphne; Lewis, Terri L. (Frontiers in Integrative Neuroscience, 2015)
Significant controversies have arisen over the developmental trajectory for the perception of global motion. Studies diverge on the age at which it becomes adult-like, with estimates ranging from as young as 3 years to as old as 16. In this article, we review these apparently conflicting results and suggest a potentially unifying hypothesis that may also account for the contradictory literature in neurodevelopmental disorders, such as Autism Spectrum Disorder. We also discuss the extent to which patterned visual input during this period is necessary for the later development of motion perception. We conclude by addressing recent studies directly comparing different types of motion integration, both in typical and atypical development, and suggest areas ripe for future research.